The Effect Of Wound Stage On Wound Healing Duration In Diabetic Ulcer Patients At The Polyclinic Of Fl Tobing Hospital, Sibolga City In 2020 - Asrina Sitompul; Jenni Susi Sihite; David Hamonangan (Institute of Computer Science (IOCS), 2020)
Patients with diabetes often experience accompanying problems. One of these problems is the emergence of wounds that are difficult to heal, where the place where injuries often occur is the lower extremities. Wounds that are difficult to heal can cause problems in diabetic feet such as ulceration, infection and gangrene. Where are things It is a common cause of hospitalization for people with diabetes. According to The National Institute of Diabetes and Digestive and Kidney Disease, that in Indonesia there are 1,785 DM patients who have experienced complications such as neuropathy (63.5%),retinopathy (42%), nephropathy (7.3%),macrovascular (16%),Microvascular (6%) and diabetic foot wounds (15%) while the mortality rate from diabetic foot ulcers and gangrene reaches 17-23% and the amputation rate reaches 15-30%, in addition the mortality rate 1 year after amputation is 14, 8%. The purpose of this study was to determine the effect of wound stage on the healing time of diabetic ulcer patients.This study was conducted using a descriptive analysis design with a cross sectional approach. The population that became the focus of this study were patients with ulcers who received wound care at the FL Tobing Hospital polyclinic as many as 85 people.The sample in this study were all patients with diabetic ulcers who visited or received wound care visits with total sampling technique. The results of the p-value statistical test based on table 4.10 are p = 0.010 >0.05, so it can be said that there is a significant influence between the final wound stage factor on the healing time of diabetic ulcers.